2015
DOI: 10.1039/c5gc00644a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free, visible-light-mediated transformation of aryl diazonium salts and (hetero)arenes: an efficient route to aryl ketones

Abstract: A visible-light-catalyzed synthesis of aryl ketones from aryldiazonium salts, CO and (hetero)arenes at room temperature is discovered. This transformation represents an efficient and attractive synthetic utilization of aryl diazonium salts.Scheme 1 Synthesis of aryl ketones via redox carbonylation. † Electronic supplementary information (ESI) available. See

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…The desired benzophenone 10.3 was formed in 74% yield aer 16 h. On the basis of these preliminary results, and those of previous studies, they proposed the mechanism shown in (Scheme 10). 50 The plausible reaction mechanism is described in Scheme 11. 51 Initially, eosin Y was converted to excited state eosin Y* upon irradiation of visible light, and this eosin Y* underwent reductive quenching by thiophenol to afford the radical cation A and form an eosin Y radical anion.…”
Section: Oxidative Synthesis Of Aryl Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The desired benzophenone 10.3 was formed in 74% yield aer 16 h. On the basis of these preliminary results, and those of previous studies, they proposed the mechanism shown in (Scheme 10). 50 The plausible reaction mechanism is described in Scheme 11. 51 Initially, eosin Y was converted to excited state eosin Y* upon irradiation of visible light, and this eosin Y* underwent reductive quenching by thiophenol to afford the radical cation A and form an eosin Y radical anion.…”
Section: Oxidative Synthesis Of Aryl Ketonesmentioning
confidence: 99%
“…The organic dye eosin Y has been found more synthetic utility in photocatalysed organic reactions due to its better yield capacity in comparison to other organic dye of uorescein family. 50 The photochemistry of eosin Y is well investigated: upon excitation by visible light, eosin Y undergoes rapid intersystem crossing to the lowest energy triplet state, which has a life time of 24 ms. [25][26][27] Eosin Y absorbs green light; the UV-Vis spectrum shows a characteristic peak at 539 nm with a molar extinction coefficient 3 ¼ 60 803 M À1 cm À1 . Upon excitation eosin Y becomes more reducing and more oxidizing compared to in its ground state.…”
Section: Introductionmentioning
confidence: 99%
“…502 The diarylketone products 161.3 could be achieved in good yields with simple arenes (161.4) and heteroarenes (161.5 and 161.6) and were proposed to form by a similar mechanism to the one shown in Scheme 160.…”
Section: Chemical Reviewsmentioning
confidence: 96%
“…Additionally, the visible-light-induced carbonylation mediated by organic dye catalysts has also been applied in the synthesis of aryl ketones. 92…”
Section: Photoinitiated Radical Carbonylation Reactionsmentioning
confidence: 99%